The Effect of Qur'an Reading in Jewawut Infusion (Setaria italica) on Changes in Cholesterol Levels: A Study in Vivo - Haniah Haniah; Khaerani Khaerani; Munirah Munirah (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
Health is the main key in carrying out of daily activities. One of the health problems and can be dangerous if not treated properly is high cholesterol levels. One of the treatment efforts is to return to the Al-Qur'an. This study aims to combine the use of ruqyah water with the recitation of the verse al-Quran with jewawut herbs to reduce cholesterol levels. The method is laboratory experimental with pre-post test by measuring cholesterol levels before and after treatment in mice. There were 5 groups used, positive control, negative control, giving ruqyah water, giving jewawut infusion, giving ruqyah water to jewawut infusion. The results of this study showed a significant difference (p <0.05) in the provision of ruqyah water to jewawut infusion.